2008
DOI: 10.1016/j.jpeds.2008.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and Neonatal Risk Factors for Sleep Disordered Breathing in School-Aged Children Born Preterm

Abstract: Objectives-Previously published data from the Cleveland Children's Sleep and Health Study (CCSHS) demonstrated that preterm infants are especially vulnerable both to sleep disordered breathing (SDB) and its neurocognitive sequelae at age 8-11 years. In this analysis, we aimed to identify the components of the neonatal medical history associated with childhood SDB among children born prematurely.Study design-This analysis focuses on the 383 children in the population-based CCSHS cohort who were born <37 weeks g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
4
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 44 publications
1
66
4
1
Order By: Relevance
“…Possible factors that may be hypothesized to contribute to OSAS in expreterm infants include palatal deformation secondary to intubation (38), hypotonia, and abnormalities in ventilatory control. Hibbs and colleagues (39) reported that neonatal methylxanthine use was associated with a twofold increase in childhood OSAS, which was not borne out in the current randomized, controlled trial.…”
Section: Discussioncontrasting
confidence: 54%
“…Possible factors that may be hypothesized to contribute to OSAS in expreterm infants include palatal deformation secondary to intubation (38), hypotonia, and abnormalities in ventilatory control. Hibbs and colleagues (39) reported that neonatal methylxanthine use was associated with a twofold increase in childhood OSAS, which was not borne out in the current randomized, controlled trial.…”
Section: Discussioncontrasting
confidence: 54%
“…Whether the functional changes reported here for the sternohyoid, namely increased force and fatigue, represent adaptive or maladaptive remodelling is less clear, but these changes may have consequences for upper airway control in later life. Our results suggest the intriguing possibility that early life hypoxia may predispose to upper airway instability in later life, including increased propensity for obstructive apnoea [34,35]. Effects of sustained hypoxia on respiratory muscle MHC fibre type and oxidative enzyme activity The mechanism for the sustained hypoxia-induced decrease in sternohyoid endurance is unknown.…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies suggest that young adults who were born preterm exhibit increased incidence of sleepdisordered breathing with apneas (34)(35)(36). Furthermore, adults (30 y of age) who had been born preterm showed an increased incidence of hypertension (37).…”
Section: Discussionmentioning
confidence: 99%